Measurement of flourishing: a scoping review - Rule, Andrew; Abbey, Cody; Wang, Huan; Rozelle, Scott; Singh, Manpreet K. (Frontiers in Psychology, 2024)
Introduction Flourishing is an evolving wellbeing construct and outcome of interest across the social and biological sciences. Despite some conceptual advancements, there remains limited consensus on how to measure flourishing, as well as how to distinguish it from closely related wellbeing constructs, such as thriving and life satisfaction. This paper aims to provide an overview and comparison of the diverse scales that have been developed to measure flourishing among adolescent and adult populations to provide recommendations for future studies seeking to use flourishing as an outcome in social and biological research. Methods In accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), we conducted a scoping review across PubMed and EMBASE of studies introducing original flourishing scales (defined as a previously unpublished measure of mental health or wellbeing that used “flourishing” in its definition). Studies focusing on adult populations that were published before April 28, 2023 were considered eligible for inclusion. Results Out of 781 studies retrieved, we identified seven eligible studies covering seven unique flourishing scales. We find that all seven scales are multidimensional and assess features over monthly or yearly intervals. While most of the scales (six out of seven) include indicators of both hedonic and eudaimonic wellbeing, the operationalization of these dimensions of wellbeing varies considerably between scales. Several of the scales have been translated and validated across multiple geographical contexts, including higher- and lower-income countries. Discussion Complementing self-report measures with other social, economic, regional, and biological indicators of flourishing may be useful to provide holistic and widely applicable measures of wellbeing. This review contributes to concept validation efforts that can guide strategies to sustain flourishing societies.